The structure of the HIV-1 Vpu ion channel: modelling and simulation studies. - Cordes, F; Kukol, A; Forrest, L; Arkin, I; Sansom, MS; Fischer, W (2001)
Vpu is an 81 amino acid auxiliary protein in HIV-1 which exhibits channel activity. We used two homo-pentameric bundles with the helical transmembrane segments derived from FTIR spectroscopy in combination with a global molecular dynamics search protocol: (i) tryptophans (W) pointing into the pore, and (ii) W facing the lipids. Two equivalent bundles have been generated using a simulated annealing via a restrained molecular dynamics simulations (SA/MD) protocol. A fifth model was generated via SA/MD with all serines facing the pore. The latter model adopts a very stable structure during the 2 ns of simulation. The stability of the models with W facing the pore depends on the starting structure. A possible gating mechanism is outlined.